2014
DOI: 10.1002/cbdv.201400172
|View full text |Cite
|
Sign up to set email alerts
|

Total Mercury in Sediments, Macrophytes, and Fish from a Shallow Steppe Lake in Eastern Austria

Abstract: During summer 2011, samples of sediment, macrophytes, and fish tissues from the shallow, slightly alkaline Lake Neusiedl, Austria, were evaluated for their total Hg content. This is the first report of Hg levels from this lake. Sediments displayed Hg contents between 0.025 and 0.113 μg g(-1) dw (dry weight), significantly correlating with the proportion of organic components pointing to a small anthropogenic impact on the lake's Hg content. Hg Levels in plants and fish were unexpectedly high: both investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…In perch, higher concentrations were found in the muscle tissue compared to liver tissue, even after correcting for lipid content. This is in line with existing literature on perch (Svobodová et al, 1999;Voigt, 2007;Jirsa et al, 2014). These results confirm the high affinity of (methyl)mercury for muscle tissue.…”
Section: Total Hg Accumulation and Internal Distributionsupporting
confidence: 92%
See 2 more Smart Citations
“…In perch, higher concentrations were found in the muscle tissue compared to liver tissue, even after correcting for lipid content. This is in line with existing literature on perch (Svobodová et al, 1999;Voigt, 2007;Jirsa et al, 2014). These results confirm the high affinity of (methyl)mercury for muscle tissue.…”
Section: Total Hg Accumulation and Internal Distributionsupporting
confidence: 92%
“…Other studies, based on data from the Eel Pollution Network of Flanders, reported concentrations between 0.005 and 1.2 µg g -1 ww in eel muscle tissue (Maes et al, 2005;Belpaire and Goemans, 2007b;Maes et al, 2008). Comparable results were found in other European studies, with concentrations in muscle tissue ranging from 0.03 to 1.4 µg g -1 ww for perch (Svobodová et al, 1999;Szefer et al, 2003;Dusek et al, 2005;Petkovšek et al, 2012;Noël et al, 2013;Jirsa et al, 2014;Foekema et al, 2016;Łuczyńska et al, 2016) and from 0.001 to 0.79 µg g -1 ww for eel (Downs et al, 1999;Edwards et al, 1999;Eira et al, 2009;Has-Schön et al, 2006;Has-Schön et al, 2008;Noël et al, 2013;Genç and Yilmaz, 2017). A very elaborate Canadian study reported median Hg concentrations of 0.32 and 0.14 µg g -1 ww in American eel (Anguilla rostrata)…”
Section: Total Hg Accumulation and Internal Distributionmentioning
confidence: 79%
See 1 more Smart Citation
“…22,23 In the framework of a study aimed to evaluate the potential impact of external sources of articial water dotation to the lake, 24 examined the occurrence and concentration level of approximately 20 organic chemicals in the estuary of the Wulka river (the main tributary) and at one spot in the open lake, in which they detected different substances at quantiable levels. 25,26 shed light on the processes behind the accumulation and distribution of mercury in sediments, macrophytes and sh. Despite their relevance, such studies build a fragmented and insufficient knowledge basis to understand the fate of the noteworthy loads of pollutants transported into the lake by the Wulka river.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of Hg content in fish have mainly dealt with Scandinavian ecosystems [12][13][14], marine environments [15][16] or the large ecosystems of American and African lakes [17][18][19][20][21]. Considerably fewer studies have dealt with Hg contamination of fish in shallow lakes in the temperate zone [22]. Only a few of these have taken into account the effect of fish size and trophic group on the content of this element in tissues [23][24][25].…”
mentioning
confidence: 99%